La dynamique économique régionale en Tunisie. Analyse structurelle-résiduelle - Amor Belhedi (Unité Mixte de Recherche 8504 Géographie-cités, 2005)
Regional dynamics are expressed through the quantitative evolution and the structural modification of the economic aggregates (indicators), employment or regional occupied population. This paper measures the spatial dynamics of the various economic activities between 1984 and 1994. The Shift-Share-Analysis of the working population between the last two censuses of 1984 and 1994 breaks up the total evolution of a given area, in three components: one due to the initial economic structure of the considered area, one concerns rather the general economic evolution of the country and one which is more specific to the given area and would return to specific factors. The analysis shows, except for some cases, significant structural contents that are expected to increase within the context of globalization, between a dynamic littoral Tunisia which has a favorable structure and an interior having one less favorable structure too.